Modifikasi Mesin Pembangkit Uap untuk Sumber Energi Pengukusan dan Pengeringan Produk Pangan - Pudjiono, Ekoyanto; Djojowasito, Gunowo; Ismail, Ismail (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2010)
One company has a cracker in Landungsari Malang open steam generating machine. Some weaknesses in the machine such that the resulting low temperature, long heating time and fuel consumption of a large or wasteful of fuel. This experiment was conducted to improve the efficient use of steam heat, namely by modifying the power plant steam into a closed system, with the hope eventually can be used not only as an energy source steaming but also to the source of energy in drying crackers. Modify and test the performance of steam powerplant, to evaluate energy efficiency, conducted at the Laboratory of Resources and Agricultural Machinery, Agricultural Engineering Department, Faculty of Agricultural Technology, Malang UB. Tests conducted with the treatment of water volume 55 liters (V1) and 69 liters (V2) andtreatment pressure of 1 atm (P1) and 2 atm (P2).Keywords : steam power plant, energy efficiency